Respuesta :
the center of the circle = (6 + 2)/2 , (3 + 1)/2 = (4,2)
diameter = sqrt ( (6-2)^2 + (3-1)^2 ) = sqrt20
radius 1/2 * sqrt20 = 1/2 * 2 * sqrt5 = sqrt 5
r^2 = 5
so the required equation is:-
(x - 4)^2 + (x - 2)^2 = 5
Its D
diameter = sqrt ( (6-2)^2 + (3-1)^2 ) = sqrt20
radius 1/2 * sqrt20 = 1/2 * 2 * sqrt5 = sqrt 5
r^2 = 5
so the required equation is:-
(x - 4)^2 + (x - 2)^2 = 5
Its D
Answer:
D
Step-by-step explanation:
(x − 6)2 + (y + 4)2 = 8
Substitute the endpoints (8, −6) and (4, −2) into the midpoint formula to find the center of the circle:
h =
8 + 4
2
= 6
k =
−6 + (−2)
2
= −4
Center: (6, −4)
Use the distance formula to find the length of the radius. Remember that the radius is
1
2
the length of the diameter:
r =
1
2
(8 − 4)2 +(−6 − (−2))2
r =
1
2
(4
2
)
r = 2
2
Substitute values into standard equation of circle:
(x − h)2 + (y − k)2 = r2
(x − 6)2 + (y − (−4)2 = (2
2
)2
(x − 6)2 + (y + 4)2 = 8